PENGARUH PENGENDALIAN INTERNAL DAN MORALITAS INDIVIDU TERHADAP KECURANGAN (FRAUD) - Luh Era Kesumawati; Ni Made Wisni Arie Pramuki (UNHI Press, 2021)
This study aims to obtain evidence of differences in the likelihood of committing fraud between individuals in the event that there are elements of internal control and no elements of internal control, differences in the likelihood of committing fraud between individuals who have a high level of morality and those who have a high level of morality low. Participants in this study were 70 cooperative managers consisting of the chairman, secretary and treasurer in all villages of Batubulan, Gianyar Regency. The research design used was an experimental design with a 2X2 factorial design. To test the hypothesis in this study, the Two Way Analysis of Variance (ANOVA) statistical test was used. The results showed that there was no difference in the likelihood of committing fraud between individuals in the event that there was an element of internal control and no element of internal control. In addition, this study also proves that there are differences in the possibility of committing fraud between individuals who have a high level of morality and those who have a low level of morality.